Stillbirth rates among Indigenous and non‐Indigenous women in Queensland, Australia: is the gap closing?. (3rd September 2014) - Ibiebele, I; Coory, M; Boyle, FM; Humphrey, M; Vlack, S; Flenady, V
<x xml:space="preserve">Abstract</x> Objective To determine whether the disparity gap is closing between stillbirth rates for Indigenous and non‐Indigenous women and to identify focal areas for future prevention efforts according to gestational age and geographic location. Design Population‐based retrospective cohort study. Setting Queensland, Australia. Population All singleton births of at least 20 weeks of gestation or at least 400 g birthweight. Methods Routinely collected data on births were obtained for the period 1995 to 2011. Indigenous and non‐Indigenous stillbirth rates and percent reduction in the gap were compared over time and by geographic location and gestational age. Main outcome measures All‐cause and cause‐specific stillbirth rates (per 1000 ongoing pregnancies). Results Over the study period there was a 57.3% reduction in the disparity gap. Although marked reductions in the gap were shown for women in regional (57.0%) and remote (56.1%) locations, these women remained at increased risk compared with those in urban regions. There was no reduction for term stillbirths. Major conditions contributing to the disparity were maternal conditions (diabetes) (relative risk [RR] 3.78, 95% confidence intervals [95% CI] 2.59–5.51), perinatal infection (RR 3.70, 95% CI 2.54–5.39), spontaneous preterm birth (RR 3.08, 95% CI 2.51–3.77), hypertension (RR 2.22, 95% CI 1.45–3.39), fetal growth restriction (RR 1.78, 95% CI 1.17–2.71) and antepartum haemorrhage (RR 1.58, 95% CI 1.13–2.22). Conclusions The gap in stillbirth rates between Indigenous and non‐Indigenous women is closing, but Indigenous women continue to be at increased risk due to a number of potentially preventable conditions. There is little change in the gap at term gestational ages.